Evaluation of Temporal and Spatial Changes in Ecological Environmental Quality on Jianghan Plain From 1990 to 2021 - Ren, Wei; Zhang, Xuesong; Peng, Hongjie (Frontiers in Environmental Science, 2022)
Located in the middle reaches of the Yangtze River, the Jianghan Plain is an important part of the middle and lower reaches of the Yangtze River Plain, and together with the Dongting Lake Plain, it is known as the Two Lake Plain. With the rapid development of urbanization in China, the impact of human activities on the ecological environment on the Jianghan Plain has become increasingly obvious in recent years, and how to timely and objectively assess the spatial and temporal changes in ecological environmental quality is of great practical significance for the sustainable development of the region and the construction of an ecological civilization. The Google Earth Engine (GEE) platform was used to optimize the reconstruction of Landsat TM/OLI images of the Jianghan Plain from 1990-2021, coupled with four indicators of the natural ecological environment, such as the NDVI, WET, NDSI and LST, to construct the remote sensing ecological index (RSEI) and evaluate the spatial and temporal changes in ecological environmental quality on the Jianghan Plain. The results showed that the mean RSEI values in 1990, 1998, 2006, 2014 and 2021 were 0.667, 0.636, 0.599, 0.621 and 0.648, respectively, indicating that the overall ecological environmental quality of the Jianghan Plain showed a decreasing trend from 1990 to 2006 and an increasing trend from 2006 to 2021. Degradation was most serious from 1990 to 1998, accounting for 44.86% of the total area, and improvement was most obvious from 2006 to 2014, accounting for 26.64% of the total area. The Moran's I values from 1990 to 2021 were 0.531, 0.529, 0.525, 0.540, and 0.545, respectively, indicating that the spatial distribution of ecological environmental quality was positively correlated. The local spatial clustering of the RSEI (LISA) showed that the H-H clustering areas on the Jianghan Plain were mainly distributed in the northern and western regions, and the L-L clustering areas were mainly distributed in the densely populated eastern regions with frequent human activities. The results can provide a theoretical basis for ecological environmental protection and improvement on the Jianghan Plain.